2012
DOI: 10.1159/000331141
|View full text |Cite
|
Sign up to set email alerts
|

Does Antidepressant Treatment Improve Cognition in Older People with Schizophrenia or Schizoaffective Disorder and Comorbid Subsyndromal Depression?

Abstract: Background: Subsyndromal symptoms of depression (SSD) in patients with schizophrenia are common and clinically important. While treatment of depression in major depressive disorder may partially ameliorate cognitive deficits, the cognitive effects of antidepressant medications in patients with schizophrenia or schizoaffective disorder and SSD are unknown. Methods: The goal of this study was to assess the impact of SSD and their treatment on cognition in participants with schizophrenia or schizoaffective disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…anxiety, insomnia and pain (Wong et al, 2016). Several studies (Chen et al, 2013;Han et al, 2011;Herrera-Guzman et al, 2010;Jorge et al, 2010;Nair et al, 2014;Rozzini et al, 2010) have shown behavioral and cognitive improvement associated with antidepressant drug usage in patients with a range of neurologic and psychiatric diagnoses, although the literature also provides instances that might question any beneficial effect of antidepressant drug usage in cognitive decline (Ardal & Hammar, 2011;Dawes et al, 2012;Kessing, Forman, & Andersen, 2011;Rosenberg et al, 2012). The possibility that these drugs might not benefit all patient populations and actually could be contributing to risk of iatrogenic cognitive decline (i.e.…”
mentioning
confidence: 99%
“…anxiety, insomnia and pain (Wong et al, 2016). Several studies (Chen et al, 2013;Han et al, 2011;Herrera-Guzman et al, 2010;Jorge et al, 2010;Nair et al, 2014;Rozzini et al, 2010) have shown behavioral and cognitive improvement associated with antidepressant drug usage in patients with a range of neurologic and psychiatric diagnoses, although the literature also provides instances that might question any beneficial effect of antidepressant drug usage in cognitive decline (Ardal & Hammar, 2011;Dawes et al, 2012;Kessing, Forman, & Andersen, 2011;Rosenberg et al, 2012). The possibility that these drugs might not benefit all patient populations and actually could be contributing to risk of iatrogenic cognitive decline (i.e.…”
mentioning
confidence: 99%
“…Using our search criteria, we identified one RCT on citalopram. In this 12‐week study of 198 patients with schizophrenia, it was found that there were no significant differences between citalopram (20 mg/day) and placebo in changes in cognition 48 . To assess patients' cognition, a test battery was used which included the MMSE, Digit Span Distractibility Test, Letter and Category Fluency, Trail‐Making Test, CPT, Digit‐Symbol‐Coding, Symbol Search, and Letter‐Number Sequencing.…”
Section: Resultsmentioning
confidence: 99%
“…In this 12-week study of 198 patients with schizophrenia, it was found that there were no significant differences between citalopram (20 mg/day) and placebo in changes in cognition. 48…”
Section: Citalopram (1 Article)mentioning
confidence: 99%
“…Many reasons lie behind the prescription of antidepressant drugs, which increased dramatically from 1999 to 2014 (5). However, some studies have questioned whether antidepressants confer any benefits in terms of cognitive decline (69). Recently, a meta-analysis indicated that antidepressant usage was associated with AD/dementia (10).…”
Section: Introductionmentioning
confidence: 99%